Question Number 122850 by liberty last updated on 20/Nov/20
$$\:\:\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\:\frac{\mathrm{4}{k}}{\mathrm{4}{k}^{\mathrm{4}} +\mathrm{1}}\:=\:? \\ $$
Answered by bemath last updated on 20/Nov/20
$$\:\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\:\frac{\left(\mathrm{2}{k}^{\mathrm{2}} +\mathrm{2}{k}+\mathrm{1}\right)−\left(\mathrm{2}{k}^{\mathrm{2}} −\mathrm{2}{k}+\mathrm{1}\right)}{\left(\mathrm{2}{k}^{\mathrm{2}} +\mathrm{2}{k}+\mathrm{1}\right)\left(\mathrm{2}{k}^{\mathrm{2}} −\mathrm{2}{k}+\mathrm{1}\right)}\:= \\ $$$$\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\left(\frac{\mathrm{1}}{\mathrm{2}{k}^{\mathrm{2}} −\mathrm{2}{k}+\mathrm{1}}\:−\:\frac{\mathrm{1}}{\mathrm{2}{k}^{\mathrm{2}} +\mathrm{2}{k}+\mathrm{1}}\right)\:= \\ $$$$\:\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\left(\frac{\mathrm{1}}{\mathrm{2}{k}^{\mathrm{2}} −\mathrm{2}{k}+\mathrm{1}}\:−\:\frac{\mathrm{1}}{\mathrm{2}\left({k}+\mathrm{1}\right)^{\mathrm{2}} −\mathrm{2}\left({k}+\mathrm{1}\right)+\mathrm{1}}\right)= \\ $$$$\:\mathrm{1}−\frac{\mathrm{1}}{\mathrm{2}{n}^{\mathrm{2}} +\mathrm{2}{n}+\mathrm{1}}\:=\:\frac{\mathrm{2}{n}^{\mathrm{2}} +\mathrm{2}{n}}{\mathrm{2}{n}^{\mathrm{2}} +\mathrm{2}{n}+\mathrm{1}} \\ $$
Answered by Dwaipayan Shikari last updated on 20/Nov/20
$$\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\frac{\mathrm{4}{k}}{\mathrm{4}{k}^{\mathrm{4}} +\mathrm{1}+\mathrm{4}{k}^{\mathrm{2}} −\mathrm{4}{k}^{\mathrm{2}} } \\ $$$$=\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\frac{\mathrm{4}{k}}{\left(\mathrm{2}{k}^{\mathrm{2}} +\mathrm{1}−\mathrm{2}{k}\right)\left(\mathrm{2}{k}^{\mathrm{2}} +\mathrm{1}+\mathrm{2}{k}\right)} \\ $$$$=\underset{{k}=\mathrm{1}} {\overset{{n}} {\sum}}\frac{\mathrm{1}}{\mathrm{2}{k}^{\mathrm{2}} −\mathrm{2}{k}+\mathrm{1}}−\frac{\mathrm{1}}{\mathrm{2}{k}^{\mathrm{2}} +\mathrm{2}{k}+\mathrm{1}} \\ $$$$=\left(\mathrm{1}−\frac{\mathrm{1}}{\mathrm{5}}+\frac{\mathrm{1}}{\mathrm{5}}−\frac{\mathrm{1}}{\mathrm{13}}+…−\frac{\mathrm{1}}{\mathrm{2}{n}^{\mathrm{2}} +\mathrm{2}{n}+\mathrm{1}}\right) \\ $$$$=\frac{\mathrm{2}{n}\left({n}+\mathrm{1}\right)}{{n}^{\mathrm{2}} +\left({n}+\mathrm{1}\right)^{\mathrm{2}} } \\ $$